The Effectiveness of Applying Handball Shooting Skills Training Model to Improve Beginner Athlete Shooting Skills - Lanos, Muhsana El Cintami; Oktariyana, Oktariyana; Lestari, Hikmah (Journal of Physical Education Health and Sport, 2021)
This research uses quantitative methods. This study aims to determine the effectiveness of the application of the handball shooting skills training model to improve the shooting skills of novice athletes. The research design in this study was the one group control pretest-posttest. The research has been carried out in several handball sports clubs in Palembang, South Sumatera. Based on the results of the test of the effectiveness of the application of the handball shooting skills training model that has been carried out, the N-Gain Score test results obtained on the results of the shooting skills obtained by an average N-Gain Score for the experimental class of 86.88% with the "effective" category, the value N-Gain Score at least 68% and maximum N-Gain Score of 100%. Meanwhile, the average N-Gain Score for the control class is 25.63% with the "ineffective" category, the minimum N-Gain Score is 8.33% and the maximum N-Gain Score is 53.85%, so it can be concluded that the application of the development model is proven. Effective so as to improve the shooting skills of novice athletes. So thus from the results of this study it is recommended to teachers, coaches and novice athletes to be able to use the product training model that has been developedÃ‚Â